2020
DOI: 10.1038/s41598-020-62414-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics in cancer revealed by Positron Emission Tomography radiomics

Abstract: Metabolic images from Positron Emission Tomography (PET) are used routinely for diagnosis, follow-up or treatment planning purposes of cancer patients. in this study we aimed at determining if radiomic features extracted from 18 F-Fluoro Deoxy Glucose (FDG) PET images could mirror tumor transcriptomics. In this study we analyzed 45 patients with locally advanced head and neck cancer (H&N) that underwent FDG-PET scans at the time of diagnosis and transcriptome analysis using RnAs from both cancer and healthy ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…We collected information from 60 articles that satisfy our selection criteria and evaluated head and neck cancer [ 28 , 82 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , ...…”
Section: Resultsmentioning
confidence: 99%
“…We collected information from 60 articles that satisfy our selection criteria and evaluated head and neck cancer [ 28 , 82 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , ...…”
Section: Resultsmentioning
confidence: 99%
“…In oncology, multimodality imaging, such as positron emission tomography (PET)-computed tomography (CT) and singlephoton emission CT, can describe both the anatomical and functional features of tumors in great detail. However, recent efforts have focused on a combination of quantitative functional assessments, such as multiple PET tracers, various magnetic resonance imaging (MRI) contrast mechanisms, and PET-MRI, thereby revealing multidimensional features of the tumor phenotype (16)(17)(18). For instance, diffusion-weighted MRI is capable of reflecting tumor density and cellularity, and can therefore be used to monitor the response to cytotoxic treatment (19).…”
Section: Acquisition Of Raw Imagesmentioning
confidence: 99%
“…In the largest radiogenomic study to date, Zhu et al reported that CT features such as volume and textural homogeneity were negatively associated with multiple innate and adaptive immune pathways, whereas the same pathways were positively associated with convexity, sphericity, and heterogeneous texture features [73]. In another recent PET radiomics study, immune system pathways were associated with both shape and texture features [74].…”
Section: Head and Neck Cancermentioning
confidence: 99%